Submitral aneurysm of varied aetiologies: a case series. Issue 2 (20th February 2021) - Prasad, Krishna; Gupta, Himanshu; Sihag, Bhupendra Kumar; Bootla, Dinakar; Panda, Prashant; Sharma, Arun; Chauhan, Rajeev; Gawalkar, Atit; Dahiya, Neelam
Abstract: Background: Submitral aneurysm is a rare disease initially described in the African population. It is usually considered congenital in origin, due to a defect in the posterior portion of the mitral annulus. However, it can be seen in other diseases like ischaemic heart disease, rheumatic heart disease, infective endocarditis, tuberculosis, and syphilis. Case presentation: Case 1 was a 29-year-old female, hypertensive undergoing maintenance haemodialysis for chronic kidney disease and on anti-tubercular therapy. She was found to have a large submitral aneurysm with severe mitral regurgitation, moderate left ventricular dysfunction, and pericardial effusion on echocardiogram. Case 2 was a 58-year-old gentleman presented with inferior wall ST-elevation myocardial infarction and was thrombolyzed with streptokinase for the same. Echocardiogram done 6 months later for evaluation of dyspnoea showed a large inferobasal aneurysm. Case 3 was a 56-year-old hypertensive presented with dyspnoea on exertion and echocardiogram showed a large posterolateral region with transmural late gadolinium enhancement. Case 4 was a 13-year-old boy presented with fever and cerebrovascular accident. Echocardiogram revealed vegetation in the mitral valve and a small submitral aneurysm with vegetation inside it. Discussion: Submitral aneurysm is usually considered congenital in origin. However, it can be due to ischaemic heart disease, rheumatic heart disease, Takayasu arteritis, and tuberculosis. Top dimensional echocardiogram is the investigation of choice. Cardiac magentic resonance imaging helps in identifying the underlying aetiology and delineating the surrounding structures.